Present and future climate change in Indian Cardamom Hills: implications for cardamom production and sustainability - Murugan, M.; Shetty, P. K.; Anandhi, Aavudai; Ravi, R. (My University, 2013)
Aims: This paper examines the interactions between climate parameters and cardamom capsule yield and its sustainability in Indian Cardamom Hills. Methodology: Temporal trends were evaluated at annual, seasonal and monthly time scale using Mann-Kendall method. Significant trends were identified at annual, seasonal and monthly scale using two tailed Z-Test. The temporal trends were evaluated using the non-parametric Mann-Kendall test. To quantify the slope we used Sen’s non-parametric estimator of slope. The significance of the test was evaluated using two tailed Z-Test. A p value of <0.05 was used to indicate statistical significance, using two tailed Z test. Results: Climate warming was significant in the recent decades in the Indian Cardamom Hills, which is recognized as one of the ecologically sensitive and biologically diverse areas. Considerable and significant spatial and temporal variations have occurred in the main climatic elements like air temperature, rainfall and relative humidity in the hill region. Significant positive trend in day-night time temperature has been observed and the trend differed from one station to another. Significant increasing trend was also observed for minimum temperature than maximum temperature and this had caused decline in diurnal temperature. Both winter and summer monsoon rainfall as well as high relative humidity had a positive influence on the yield of cardamom. However, the variability in these two types of rainfall was high for the entire region and the trend is negative. The variability of monthly mean precipitation is high for May, December and January under AR4 climate scenario. Conclusion: The sustainable yield of cardamom may be possible only when the winter and summer rainfall variabilities were minimal. Increasing trend of soil temperature from 0-10 cm depth was recorded, which was significant at 5 cm depth and can cause considerable negative implications for sustainable cardamom production both in terms of reduced soil moisture availability and altered pest population dynamics.
Citation: Murugan, M., P. K. Shetty, A. Anandhi, and R. Ravi. “Present and Future Climate Change in Indian Cardamom Hills: Implications for Cardamom Production and Sustainability.” British Journal of Environment & Climate Change 2, no. 4 (January 19, 2013): 368–90.
Keywords: Temperature; Rainfall; Relative humidity; Soil temperature; Cardamom